Energy Efficient Low-Cost Housing in Ho Chi Minh using EDGE Buildings. Issue 1 (July 2020) - Rahmadyani, Helfa; Suhendri,
Abstract: Various forecasts on the urbanization rate in the world state that more than 50% of the world's population will live in cities by 2030. In the condition of land scarcity i.e. the land availability in the city is limited, a compact development is needed. Compact development will be closely related to Transit-Oriented Development (TOD). Transit-oriented development is not only about transit, but consisting of mixture development of housing, office, retail, and/or other amenities. In this type of development, vertical housing is unavoidable, including housing schemes for a low-income citizen, thus well-performed low-cost housing is important to be studied. Among the numerous studies, some focus on the construction materials and methods, some others on the comfort and health aspect, more on the management of the building, and not least focus on energy consumption of the housing building. This study develops an energy-efficient low-cost apartment through the calculation of various passive and active design strategies. The study uses two parameters i.e. energy saving percentage and incremental cost to determine the most optimal combination strategies. The case study in this research is in Ho Chi Minh City, Vietnam. The comparison of the design alternatives is done quantitatively using EDGE Buildings. The combination of low-cost housing design strategies can save energy by 49.86% with an incremental cost of 27, 598, 581 VND and the payback period in 5.21 years.